A interatividade na rede social Wattpad : uma experiência no ensino de língua inglesa - Santos, Giulia Pereira (2022)
The Internet has become a space for creation and construction of content and meaning. Society and school, for being immersed in hypermobility and ubiquity, have incorporated much of the profound changes in the forms of communication and teaching that we have experienced. This dissertation aims to understand the interactivity in the text production of elementary school students, in the social writing network Wattpad, in order to promote the teaching of reading and writing in English as a social practice. This study is characterized as qualitative research, for focusing on the understanding and interpretation of the phenomenon that is also identified as a Pedagogical Intervention Research. The data are generated in a state school located in the metropolitan region of Aracaju, through the creation of a reading exchange group about textual productions on Wattpad, in which 14 students from the 8th and 9th grades of elementary school participated. The feedbacks exchanged in the reading groups, the researcher's field diary, the audio recordings of the writing workshops, the questionnaires implemented at the beginning of the research, and the semi-structured interviews are the data generation instruments selected for this study. The data analysis procedures are based on Freeman (1998), whose principles consider the teacher-researcher practice in two ways: one in which the teacher is an external investigator of the school reality and one in which the teacher is a participant-integrant of the environment. In this case, in this research both positions were contemplated, since it has the look of a teacher-investigator from outside the ordinary routine of the school who also conducted workshops for a determined time in the investigation context. The results show that interactivity had different repercussions on the students' learning. While the participants who were already involved in digital practices outside of school were able to interact more with each other, the students who did not have technical skills, for socioeconomic reasons, were not able to complete the proposed activities or develop their language skills. The data points the need for the use of digital technologies and literacies such as those of the reading exchange groups to decrease the social and technological inequality that is present in Brazilian public schools and negate the democratic decision of the students to expand their intellectual perspectives.